Circadian Dysregulation of the TGFβ/SMAD4 Pathway Modulates Metastatic Properties and Cell Fate Decisions in Pancreatic Cancer Cells - Li, Yin (iScience, 2020)
Impairment of circadian rhythms impacts carcinogenesis. SMAD4, a clock-controlled gene and central component of the TGFβ canonical pathway, is frequently mutated in pancreatic ductal adenocarcinoma (PDA), leading to decreased survival. Here, we used an in vitro PDA model of SMAD4-positive and SMAD4-negative cells to investigate the interplay between circadian rhythms, the TGFβ canonical signaling pathway, and its impact on tumor malignancy. Our data show that TGFβ1, SMAD3, SMAD4, and SMAD7 oscillate in a circadian fashion in SMAD4-positive PDA cells, whereas altering the clock impairs the mRNA dynamics of these genes. Furthermore, the expression of the clock genes DEC1, DEC2, and CRY1 varied depending on SMAD4 status. TGFβ pathway activation resulted in an altered clock, cell-cycle arrest, accelerated apoptosis rate, enhanced invasiveness, and chemosensitivity. Our data suggest that the impact of TGFβ on the clock is SMAD4-dependent, and SMAD3, SMAD4, DEC1, and CRY1 involved in this cross-talk affect PDA patient survival.